2021
DOI: 10.1111/febs.16089
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles of super enhancers in inflammatory gene transcription

Abstract: Acute and chronic inflammation is a basic pathological event that contributes to atherosclerosis, cancer, infectious diseases, and immune disorders. Inflammation is an adaptive process to both external and internal stimuli experienced by the human body. Although the mechanism of gene transcription is highly complicated and orchestrated in a timely and spatial manner, recent developments in next-generation sequencing, genomeediting, cryo-electron microscopy, and single cell-based technologies could provide us w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…One of the most evident features of acute inflammation is the expression and release of proinflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), and the expression of cyclooxygenase (COX), an enzyme implicated in the synthesis of prostaglandins (PGs) and therefore in the transition to and the maintenance of chronic inflammation [3]. This cascade of events, when unregulated, is widely considered an important pathogenic factor contributing to chronic-degenerative diseases including cardiovascular diseases, diabetes, Alzheimer's, rheumatoid arthritis, chronic obstructive pulmonary diseases, some specific types of cancer, chronic kidney diseases or obesity [4,5]. In the presence of unregulated inflammatory response, proinflammatory and anti-inflammatory pathways are leading to a complex pattern of systemic activations consequent to cytokine storm, resulting in immune system impairment and proinflammatory imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most evident features of acute inflammation is the expression and release of proinflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), and the expression of cyclooxygenase (COX), an enzyme implicated in the synthesis of prostaglandins (PGs) and therefore in the transition to and the maintenance of chronic inflammation [3]. This cascade of events, when unregulated, is widely considered an important pathogenic factor contributing to chronic-degenerative diseases including cardiovascular diseases, diabetes, Alzheimer's, rheumatoid arthritis, chronic obstructive pulmonary diseases, some specific types of cancer, chronic kidney diseases or obesity [4,5]. In the presence of unregulated inflammatory response, proinflammatory and anti-inflammatory pathways are leading to a complex pattern of systemic activations consequent to cytokine storm, resulting in immune system impairment and proinflammatory imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…BET proteins are known to bind with super-enhancers and modulate super-enhancers’ function in inflammatory conditions. 111 , [147] , [148] , [149] , [150] BET proteins recognise the acetyl group on tagged histone lysine residues through their BRD. Four BET proteins have been described, one of which is germ cell-specific (BRDT), with the other 3 being expressed ubiquitously (BRD2, BRD3, and BRD4).…”
Section: Clinical Implications Of the Study Of Epigenetics In Arldmentioning
confidence: 99%
“…Recent studies have suggested that bio-macromolecular condensates form at super-enhancers (SEs) [ 81 , 96 , 97 , 100 , 101 ]. This model was supported inter alia by the ability of BRD4 and MED1, a key component of SEs, to form condensates at sites of SE-driven transcription.…”
Section: Transcription Regulators and Liquid–liquid Phase Separationmentioning
confidence: 99%